Hubungan Kebiasaan Jajan Dan Pola Makan Dengan Status Gizi Anak Di Tk Asri Palembang Tahun 2022 - Herliani, Deska (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Nutritional status is one of the important elements in shaping health status. Nutritional status is a condition caused by a balance between nutrient intake from food and the body's nutritional needs. Nutritional status is strongly influenced by nutritional intake. This study aims to determine the relationship between snacking habits and eating patterns with the nutritional status of children in TK IT ASRI Palembang in 2022. The design of this study was a quantitative method with a cross sectional design. The number of samples in this study were 48 respondents. The sample was taken using the total sampling method. The results showed that there was a relationship between snacking habits and the incidence of nutritional status with a p value of 0.002 (OR=19.429), and there was a relationship between eating patterns and nutritional status with a p value of 0.027 (OR=5.714). The results of the study concluded that there was a significant relationship between snacking habits and eating patterns with nutritional status. It is recommended to conduct a program to monitor nutritional and health status on a regular basis as well as provide counseling or education on the consumption of balanced nutritious food to parents.